Differential Pasting and Rheological Properties of Diverse Underutilized Starches Modified by Acetic Anhydride and Vinyl Acetate - Song Xu; Bilatu Agza Gebre; Chuangchuang Zhang; Solomon Abate Mekonnen; Mengting Ma; Hui Zhang; Zhongquan Sui; Harold Corke (Foods, 2025)
Underutilized starch sources are gaining increasing recognition. However, the inherent functional deficiencies of native starch have limited its application in food industry. To counteract the deficiencies in its native characteristics, starch can be modified by acetylation. Two waxy starches (proso millet and amaranth) and four non-waxy starches (foxtail millet, quinoa, buckwheat, and oat) were modified by acetic anhydride and vinyl acetate, respectively. Degree of substitution of acetylated starches revealed that granule size did not significantly affect acetylation efficiency in starches from different plant origins. Acetylation increased peak and final viscosity of starches, with vinyl acetate exhibiting a more pronounced effect than acetic anhydride. Acetic anhydride decreased K and increased n values of non-waxy starches, showing reduced thickening ability. In contrast, vinyl acetate modification showed opposite trends, suggesting increased viscosity and pseudoplasticity. For non-waxy starches, G′25°C, G′0.1Hz, G′20Hz and gel hardness decreased after acetylation, indicating that acetylation contributed to a less solid and less elastic gel network. The extent of change in vinyl acetate modification was more pronounced than that of acetic anhydride. For waxy starch, vinyl acetate modification decreased tan δ25°C and increased gel hardness. In summary, acetylation reagent type was the major factor determining the pasting properties of acetylated starch, but the presence or absence of amylose would influence the rheological and gel properties of acetic anhydride and vinyl acetate modified starches. These findings could help unlock the potential applications of acetylated underutilized starches in the food industry.